(untitled) (Eurasian Journal of Research, Development and Innovation, 2022)
The current study aims at Evaluating the Preparatory EFL English Course ( Book 6) for Iraqi Islamic Schools. The sample of the study includes fifty-four teachers (34 boys(63%) and 20 girls(37%) )who are actually teaching English in the selected schools during the academic year 2018-2019 (in the Islamic schools ) in the city of Baghdad and Kirkuk who represent 77% of the total number of teachers’ population. A questionnaire has been conducted and applied to the selected sample. The required data are collected and analysed statistically. The study reaches to results such as , ( Book6) does not supply students with the skills of writing and listening at the same time